Women's perspectives on resilience and research on resilience in motherhood: A qualitative study - Susan Hannon; Agnes Higgins; Déirdre Daly (Wiley, 2023)
Abstract Purpose Definitional perspectives and operational approaches to the concept of resilience vary within the literature; however, little is known of women's opinions on current resilience research, or the philosophical and methodological directions women believe such research should take. This research explored women's perspectives on resilience research in the perinatal period and early motherhood and sought their opinions on the ways in which they believe research should be advanced. Methods Following ethical approval, online interviews were conducted with 14 ethnically and socioeconomically diverse women who were mothers. Findings from a concept analysis on resilience in pregnancy and early motherhood, conducted by the authors, were shared with women before and during the interview. Interviews were organised in sections corresponding to the findings within the concept analysis' four philosophical (Epistemology, Linguistic, Logic, Pragmatic) principles and thematically analysed. Results Epistemology-Women endorsed a dynamic process definition, and viewed resilience as influenced by multilevel, multisystemic processes. Linguistic-Women viewed words such as 'adaptation' and 'adjustment' as being more active and empowering than the term 'coping' in relation to motherhood. Logic-Women were resistant to the predominant operational conceptualisation of resilience as illness absence. Pragmatic-Women were wary of resilience research being used to reduce mental health support for other mothers and families. Conclusions Women provided constructive criticisms on the current state of resilience literature. Women suggested actionable ways in which research may be developed to better align with the epistemological and ethical approaches women want to see in resilience and maternal mental health research. Patient or Public Contribution Women who are mothers and participants in health research were consulted on their views of trends in mental health and resilience research in motherhood.